Estudio de Viabilidad de un Turbogenerador de 6 Mega Watts en el Ingenio El General Milton Fonseca. - Castro-Valverde, Anthony (Instituto Tecnológico de Costa Rica, 2018)
In the present project, a viability study was developed for the installation of a 6MW turbo generator in the sugar mill, General Milton Fonseca. The main objective of the project is to separate the company from the national electricity grid and also to avoid consumption and demand expenses, contemplating projected extensions. The main problem is that there is not enough steam available to generate more electricity, which is why loads must be handled to define which equipment (turbines) to replace with electric motors, to take the steam from the turbines and redirect it to the new generation equipment, the electrification of motors leads to an increase in power, which must be supported by the turbo generator. The present work contemplates four great works.  Charges balance of the steam network.  Charges balance of the electric network.  Equipment selection.  Total cost of the work. Once the option that best adapts to the needs and conditions of the company has been selected, the economic analysis is carried out in which the financial viability of the project is determined. Finally, the technical, economic and reliability case are evaluated to determine if it is viable to invest in the project.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Gestión; Vapor; Viabilidad; Turbogeneradores; Research Subject Categories::TECHNOLOGY::Engineering mechanics